Edwardsiella tarda septicemia with underlying multiple liver abscesses - Rathor, Mohammad Yousuf; How, Soon Hin; Abdul Rashid, Mohd Amran; Hla, K.T; Shah, Anis; Francis, A. (College of Pathologists, Academy of Medicine Malaysia, 2006)
Edwardsiella tarda has recently been described as a member of the family Enterobacteriaceae. The genus Edwardsiella contains three species; E. hoshinae, E. ictaluri and E. tarda. Edwardsiella tarda is the only species which has been recognised as pathogenic to humans, especially in those with an underlying disease. The most common presentation is watery diarrhoea. Extra intestinal infections have been reported infrequently. Humans seem to be infected or colonised with Edwardsiella through ingestion or inoculation of a wound. This report is of a patient with multiple liver abscesses due to E. tarda who later developed bacterial peritonitis and septicaemic shock.